Analysis of gas-fired NH3-H2O generator with cross flow gas burner. (25th January 2016) - Aprile, Marcello; Toppi, Tommaso; Guerra, Marco; Motta, Mario
Highlights: The gas-fired generator of a NH3 -H2 O absorption heat pump is modeled. Its performances are numerically investigated at design and off-design conditions. Distance from saturation of the feed and jacket losses become critical at partial load. Combustion efficiency, based on HHV, varied with gas input between 0.82 and 0.85. Abstract: This paper presents a model to simulate the combined heat and mass transfer processes that occur in a gas-fired generator of an ammonia water absorption heat pump. The model comprises three interconnected components: the gas furnace, the distillation column and the rectifier. The furnace is modeled like a well-stirred single volume. The distillation column and the rectifier are discretized along their axial dimension. Several heat transfer mechanisms are simultaneously solved: radiative and convective heat transfer between combustion products and generator finned surface, flow boiling and pool boiling in the two-phase ammonia water mixture inside the distillation column. The model is applied to operating conditions of interest in real applications. The generated outputs provide insight on the internal gradients, the quantification of gas furnace efficiency, and effectiveness of solution boiling and internal heat recovery. The model can be used for the simulation of absorption heat pumps with modulating gas burners.